Identifikasi dan Analisa Risiko Keselamatan dan Kesehatan Kerja (K3) Menggunakan Metode HIRARC pada PT. X - Jannah, Nurul Huda; Herwanto, Dene (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
X is a company that produces packaging bottles and does not have an OHS expert or Health, Safety and Environment (HSE) Department, so it cannot detect the risks that have the potential to cause work accidents that occur at PT. X. Therefore, it is necessary to identify the risks and hazards of work accidents in the work environment with Hazard Identification, Risk Analysis, and Risk Control (HIRARC), this method is a method used to identify the risk of work accidents by identifying, providing risk levels and risk control as an implementation of the K3 Management System (SMK3) in the company. There are 3 work activities identified with 27 risks and hazards of work accidents that occur. The assessment results show that there are 10 risks at a moderate level, 14 risks at a high level, and 3 risks at a very high level. Risk control using 5 hierarchies of risk control Elimination, substitution, Engineering Control, Administrative Controls, and the use of Personal Protective Equipment (PPE). Keywords: Occupational Safety and Health (OSH), Occupational Risk Hazard, Hazard Identification, Risk Analysis, and Risk Control (HIRARC)